OPTIMASI BUKAAN DENGAN MEMANFAATKAN EFEK WIND TUNNEL PADA RUMAH DERET, KASUS STUDI : KAMPUNG DERET PETOGOGAN, JAKARTA: https://doi.org/10.25124/idealog.v3i2.1422 - Oktovianto, Anggi (Universitas Telkom, 2018)
Energyconsumptionon domestic uses in Indonesia provokes designers to implement passive design concept as an effort to reduce the use of mechanical and electrical solution for household comfort. This research observed KampungDeretPetogoganwhich a wind tunneleffect could not accurately provide natural comfort inside the row houses. Openings design was a key element to determineoptimization of air movement indoors, including its positions, types, and dimensions. Thegoals wereto identify the causes and determine ideal openings design to optimize air circulation indoors. First assessmentinvolvedrelevantdesign theories that conducted as guidelines. Then the existed design openings were examined and compared with guidelines, thus the ideal design openings were generated. The final results concluded multiple solutions for optimizing air movement control. Anaddition of wing wall, to help control the air movement. Repositioning the openings, both on walls and roofs. The selection of opening types which would be suitable basedonairmovement pattern. Lastly, redesign the dimension of the openings to fit the needs of natural comfort inside the houses.